2017
DOI: 10.1016/j.quaint.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Poison, plants and Palaeolithic hunters. An analytical method to investigate the presence of plant poison on archaeological artefacts

Abstract: In this paper we present the development of a method for the detection of toxic substances on ancient arrow points. The aim is to go back in time until the Palaeolithic period in order to determine if poisonous substances were used to enhance the hunting weapons.The ethnographic documentation demonstrates that hunters of every latitude poisoned their weapons with toxic substances derived from plants and occasionally from animals. This highlights that often the weapons would be rather ineffective if the tips we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Jones (2007) has also summarized a wide variety of ethnohistoric and ethnographic data that document more extensive use of poisoned projectiles in North America than is usually considered (see also Ellis 1997; Flannery 1939:19, 71, 95; Quigley 1956; Van Wyk 2015; Weslager 1973:105–12). Also, Weissner (1983:261–263) has demonstrated a correlation between point size and use of poisons in southern Africa with smaller points associated with the use of various poisons (see also Borgia 2017; Lombard 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Jones (2007) has also summarized a wide variety of ethnohistoric and ethnographic data that document more extensive use of poisoned projectiles in North America than is usually considered (see also Ellis 1997; Flannery 1939:19, 71, 95; Quigley 1956; Van Wyk 2015; Weslager 1973:105–12). Also, Weissner (1983:261–263) has demonstrated a correlation between point size and use of poisons in southern Africa with smaller points associated with the use of various poisons (see also Borgia 2017; Lombard 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the possibility that poison was applied on bone arrowpoints from El Alto 5 is open. However, residue analysis should be conducted before any decisive functional label is assigned to this substance (see Borgia et al 2017) and poison recipes also need to be closely explored (Jolís 1972(Jolís [1789 Although the raw material was the by-products of food consumption, the manufacturing of the bone projectile points required a high manufacture effort, showing that late prehispanic groups elaborated costly, standardized and reliable tools for warfare. Experiments carried out by Zhilin (2015) showed that, once bone has been softened in water for two months, it took about 3-4 hours to produce a needle-like arrowpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled to this problem is the fact that most arrow poisons, at least those we know of from the ethno-historical record, were actually complex recipes, comprising many ingredients and preparatory steps 10 , 14 , 15 , and which differed from region to region 16 , 17 . Some non-toxic ingredients were also added for their adhesive properties, or simply because they were believed to impart certain effects 18 20 . For example, trapdoor spiders were ground up whole and mixed with other ingredients 21 .…”
Section: Introductionmentioning
confidence: 99%